An intervention design for promoting quality of life among patients with multiple sclerosis: a protocol with a planning approach for a mixed methods study - Atefeh Zahra HomayunHosseini (BMC Neurology, 2023)
Abstract Background Multiple sclerosis is a chronic progressive disease of the central nervous system that affects the patients' quality of life. The disease's complications reduce the quality of life in patients by creating physical, psychological, social and economic problems for the patient and his/her family and reducing the patient's individual and social functioning. The aim of the present study is designing, implementing and evaluating an intervention based on the PRECEDE-PROCEED model to promote the quality of life in people with multiple sclerosis. This paper summarizes the study protocol. Methods We will use the PRECEDE-PROCEED model for designing the study. In the first step, the factors affecting quality of life in people with multiple sclerosis will be determined by a qualitative study. In the second step, these factors will be prioritized based on their importance and variability, then behavioral and environmental factors of the most important priority will be identified. In the third step, the predisposing, enabling and reinforcing factors related to the identified priority will be determined by a qualitative directed content analysis. In the fourth step, a questionnaire will be designed and psychometric based on the results of the previous step. The fifth step will be about planning to implement the intervention. In the sixth step, the intervention will be implemented and its effectiveness will be evaluated by process, impact and outcome evaluations. Discussion The results of this study will provide information about patients' needs and concerns and thus will contribute to policymakers, government, community, health professionals and families to take the necessary measures to improve quality of life in these patients.